UJI EFEKTIFITAS PENGGUNAAN DAUN SALAM (Syzygium Polyanthum) DAN MADU SERTA NACL 0,9% TERHADAP PROSES PENYEMBUHAN LUKA AKUT PADA TIKUS PUTIH (Rattus Norvegicus Strain Wistar) - Suriadi Suriadi; Imran Imran; Ardyan Wanto Hadi (Sekolah Tinggi Ilmu Keperawatan Muhammadiyah Pontianak, 2014)
Background: Bay leaf (Syzygium polyanthum) contains flavonoids, saponins, tannins, carbohydrates, vitamin A, vitamin C, calcium and iron, while honey contains various classes of nutrients such as protein, carbohydrates, vitamin B1, vitamin C, phosphorus and iron has a healing effect on wounds. The content contained within the bay leaves and honey is able to give the effect of re- epithelialization of skin tissue damaged as a result of acute injury. Objectives: This study aims to determine the effectiveness of the test bay leaves and honey and nacl 0.9 % as a control for acute wound healing in male white rats (Rattus norvegicus Wistar strain). Methods: The research method uses a form of quasi-experimental studies (Quasy-Experiment Design) and posttest study design used is the Only Design. Manufacture of bay leaf extraction by maceration method and used as many as 15 test animals were divided into 3 treatment groups, namely treatment bay leaf, honey treatment group and the group treated with nacl 0.9 %. Acute wounds in the back right and left with a diameter of 1 cm were treated and observed the healing effects for 6 days. Results: The results showed that from day 1 to day 6 observation of acute wounds suffered diminution in diameter but no significant difference of the three treatments. Conclusion: It was concluded that the bay leaves and honey and 0.9 % NaCl effect on wound healing, but the use of bay leaves is no more effective than honey and 0.9 % NaCl.